Examining Students’ Ability to Identify Cognitive Learning Theories through the Case Analysis Game with Rotation (CAGeR) - Nuzulira Janeusse Fratiwi; Winny Liliawati; Nur Habib Muhammad Iqbal; Fanni Zulaiha (Jurnal Pendidikan Fisika dan Sains (JPFS), 2026)
Understanding learning theories is essential for prospective teachers, yet students often experience difficulties identifying theoretical perspectives within authentic instructional situations. This study aims to examine students’ ability to identify cognitive learning theories through a case-based game activity involving rotating case analysis. The study employed a descriptive qualitative design. The participants were sixteen undergraduate students in a physics education program who worked collaboratively in four groups. Students analysed four instructional cases representing different cognitive learning theories and provided written explanations for their answers. The results show that all groups correctly identified the theory represented in the misconception case. Most groups also successfully recognized the discovery learning situation. However, only half of the groups correctly identified the theories related to instructional organization and problem solving. These findings suggest that students are more familiar with learning situations involving conceptual conflict and discovery learning than with those related to instructional structure and hierarchical learning processes. The activity provided opportunities for students to interpret teaching situations and connect theoretical concepts with classroom practices.